Konsep Pendidikan Karakter Anak dalam Keluarga Disorot dari Surat Apostolik “Amoris Laetitia” - Kwirinus, Dismas (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
The focus of this research examines the concept of character education of children in the family highlighted from the apostolic letter of Amoris Laetitia. The topic of the study related to character education contained in